2014
DOI: 10.1098/rsif.2014.0416
|View full text |Cite
|
Sign up to set email alerts
|

An explicit immunogenetic model of gastrointestinal nematode infection in sheep

Abstract: Gastrointestinal nematodes are a global cause of disease and death in humans, wildlife and livestock. Livestock infection has historically been controlled with anthelmintic drugs, but the development of resistance means that alternative controls are needed. The most promising alternatives are vaccination, nutritional supplementation and selective breeding, all of which act by enhancing the immune response. Currently, control planning is hampered by reliance on the faecal egg count (FEC), which suffers from low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…For instance, sheep IgA was found to regulate Teladorsagia circumcincta growth and eggs in utero (Henderson & Stear, ; Stear et al, ). IgA was also suggested to be a good indicator of heritable host resistance to helminths (Prada Jiménez de Cisneros et al, ; Strain et al, ). We previously showed that IgA is important for the control of T. retortaeformis intensity of infection (Takar et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, sheep IgA was found to regulate Teladorsagia circumcincta growth and eggs in utero (Henderson & Stear, ; Stear et al, ). IgA was also suggested to be a good indicator of heritable host resistance to helminths (Prada Jiménez de Cisneros et al, ; Strain et al, ). We previously showed that IgA is important for the control of T. retortaeformis intensity of infection (Takar et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, sheep IgA was found to regulate Teladorsagia circumcincta growth and eggs in utero (Henderson & Stear, 2006;Stear et al, 2004). IgA was also suggested to be a good indicator of heritable host resistance to helminths (Prada Jiménez de Cisneros et al, 2014;Strain et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our model, which has been fitted to field data from Scottish salmon farms [ 34 ] and parametrized using field trials to assess genetic variation in susceptibility, breeding for resistance to sea lice would reduce levels of infective larvae by reducing the number of individuals with high numbers of lice. This environmental benefit is not captured in traditional methods of estimating the response to selective breeding and was achieved by integrating quantitative genetics into an epidemiological model [ 47 49 ], allowing genetic variation between individuals and selective breeding to be modelled.…”
Section: Discussionmentioning
confidence: 99%
“…As with parasite establishment, the fecundity (eggs/female) was assumed to decline towards a plateau as immunity was acquired ( Michel, 1969 ). The immune response effect on fecundity was assumed to develop at a different rate to the establishment and mortality due to different underlying immune mechanisms ( Stear et al, 1995 , Prada Jiménez de Cisneros et al, 2014 ). As with EM the eggs per female was plotted against larvaldays from the experiment A of Michel (1969) ; the data suggest an exponential relationship between larvaldays and fecundity ( F ), taking the form: where F max is the maximum number of eggs per female worm, F min is the minimum number of eggs per female worm and k F is the constant of the relationship between larvaldays and fecundity.…”
Section: Methodsmentioning
confidence: 99%